Theoretical study of IR spectra of paraphenylenediamine - AKALIN, ELİF; AKYÜZ, SEVİM (Elsevier, 2000)
Normal coordinate analysis of the paraphenylenediamine (1,4-diaminobenzene, PPD) molecule has been carried out and complete interpretation of the vibrational spectrum is given for both trans and cis isomers. The reliable force field and electro-optical parameters of PPD have been determined by refinement in order to fit the experimental wavenumbers and intensities of PPD molecule. The initial force field parameters of PPD were refined from the corresponding parameters of aniline molecule. The initial values of bond dipole moments of the molecule were calculated by MINDO/3 method. The combination of the calculated IR spectra of trans and cis isomers of PPD is found to reproduce the experimental IR spectrum of solid PPD, satisfactorily, indicating that PPD exists as a mixture of both conformations.
Keywords: Normal coordinate analysis; Paraphenylenediamine; Diaminobenzene; IR spectrum; Force field and electro-optical parameters